Thorndike-Barnhart beginning dictionary - Thorndike, Edward L. (Edward Lee), 1874-1949 (Scott, Foresman and Company, 1952)
A beginning dictionary for fourth and fifth graders, including illustrations and examples of usage in the definitions, and exercises and lessons teaching use of a dictionary.